Mastering openFrameworks : creative coding demystified : a practical guide to creating audiovisual interactive projects with low-level data processing using openFrameworks /: creative coding demystified : a practical guide to creating audiovisual interactive projects with low-level data processing using openFrameworks. (2013) - Unknown
No abstract available